PERAN GURU PADA PENGGUNAAN MEDIA GAMBAR DALAM PEMBELAJARAN BAHASA INDONESIA SISWA KELAS 5 SD NEGERI 200107 PADANGSIDIMPUAN - Rika Syartika Lubis; Nursyaidah Nursyaidah (Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Padangsidimpuan, 2022)
The background of this research is that students are not enthusiastic in participating in the learning process because the learning process is very monotonous and more teacher-centered, thus giving students a feeling of boredom and boredom. Therefore, teachers need to use image media to bridge the material gap in learning. So, researchers are encouraged to conduct research to find out what roles are played by fifth grade teachers in SD 200107 in the use of image media. The formulation of this problem is What is the teacher's role in the use of picture media in Indonesian subjects at SD Negeri 200107 Padangsidimpuan? How to use picture media in Indonesian subjects at SD Negeri 200107 Padangsidimpuan? This study aims to determine the role of teachers in the use of image media in SD 200107 Padangsidimpuan. The method used in this research is qualitative by using data collection techniques in the form of observation and interviews. Checking the data using traguulation. The data were analyzed through the steps of data collection, data reduction, data presentation, and conclusion drawing. Respondents in this study were fifth grade teachers, fifth grade students and the principal of SD Negeri 200107. The results of this study indicate that the fifth grade teacher has carried out his role as a motivator, educator, and facilitator but has not been optimal in his role as a facilitator because the teacher facilitates very simple media in utilizing image media in the learning process on printed media advertising materials. The way students use image media are: Making image media as a tool in understanding the subject matter, Observing image media, Explaining image media. The way the teacher uses the image media is: Preparing to use the image media, selecting the image media according to the material, the teacher being careful in explaining the material with the image media, and involving students in using the image media.Keywords: teacher's role, use of picture media.